Acute Flaccid Paralysis surveillance in Gaza Strip, Palestine - Khaled A Abu Ali (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2021)
Acute Flaccid Paralysis (AFP) is a clinical syndrome characterized by rapid onset of weakness, in the respiratory muscles, swallowing and limbs; and death because of respiratory muscles failure. AFP surveillance is crucial, the clinicians are required to notify AFP cases among children below 15 years old to the epidemiology department with completion of AFP surveillance form. In this study, the researcher analyzed AFP surveillance investigation forms to determine the clinical picture, viral etiology and the incidence of AFP among children under 15 years. Material and method (Study design): The research study conducted through cross sectional study, based on AFP investigation forms in the epidemiology department. Results: The final diagnosis of the cases were as follow, 71.1% "27 cases" were GBS, 10.5 % were Encephalitis, 7.9% were Neuropathy, 2.6% " one case only" for each of the following Aseptic meningitis, Transverse myelitis, Tuphus fever and Subspinal muscular atrophy. The incidence rate among children less than 15 years old which range from 0.58 / 100.000 in 2006 to 1.2 / 100.000 in 2012; Most of the cases 89.5 % had fully vaccinated and 10.5% had not fully vaccinated due to their ages less than one year, 65.8 "25 cases" had residual weakness, all of the cases classified as discarded according to the expert committee decision; no one case dead, all of the samples sent to the Tal-Hashomir laboratory in the occupied land in 1948 for viral isolation; most of the results 81.6% revealed that no virus isolated, 11.8% isolated ECHO virus, 2.6% isolated Coxsachie virus and 4 % isolated NPEV. Conclusion: No wild polio virus in Palestine which is polio free since 1984 and certified in 2006, our success being attributed to: start of 2 doses of IPV and 5 doses of OPV since 1978, high immunization coverage more than 95% at district level and effective AFP surveillance system in Palestine. The study recommended to encourage polio immunization and all clinicians are required to report all AFP cases and submitting at least two stool samples to the epidemiology department (at least 24 hours apart within 14 days of onset of paralysis).